Influence of the rearing system on the ileum microbiome, metabolome, and transcriptome in meat rabbits - Wu, Zhoulin; Li, Xiaoyu; Xu, Maoqin; Wen, Bin; Fu, Xiangchao; Tang, Zhonghua; Liu, Xueqin; Zhang, Jiamin (Frontiers in Veterinary Science, 2024)
The rearing system of livestock plays a vital role in animal production, meat quality, and overall welfare. This study aimed to assess the influence of cage-rearing system and forest-rearing system on the ileum microbiota, metabolome, and ileal mucosa transcriptome in meat rabbits. Moreover, 16S rDNA sequencing revealed significant differences in the ileal microbiome composition: caged rabbits exhibited a higher abundance of the genera uncultured Erysipelotrichaceae and Delftia, whereas the levels of Muribaculaceae, unclassified Burkholderiales, and uncultured Eubacteriaceae were lower compared to rabbits reared in the forest. Metabolome analysis identified 372 differentially accumulated metabolites in the ileum content, which were predominantly mapped to amino acid metabolism, nucleotide metabolism, and energy metabolism pathways. The cage-rearing system was found to positively correlate with the efficient utilization of nutrient sources. Additionally, transcriptome analysis of the ileal mucosa revealed 984 differentially expressed genes, predominantly involved in metabolic pathways, signal transduction pathways, and immune response processes. Through Pearson correlation analysis, we were able to elucidate the metabolic pathway, immune responses, and disease resistance mechanisms were affected by the rearing system. Overall, the findings suggested that metabolic adaptation, nutrient utilization, and immune response play crucial roles in how rabbits adjust to different rearing systems. While the cage system may enhance nutrient efficiency, it appears to suppress immune function and disease resistance.